THE STUDY OF UNEMPLOYMENT IN BUSINESS PERSPECTIVE IN INDONESIA - Ega Leovani; Florentinus Heru Ismadi (Journal of Finance, Economics and Business, 2023)
Unemployment in Indonesia is a problem with an urgency to provide a solution to improve social life. As unemployment increases, the poverty rate also increases. The purpose of this study is to identify and explain and overcome poverty and unemployment in Indonesian society. Efforts to reduce the unemployment rate and concomitantly reduce the poverty rate are equally important. The results of the study recommend that policy making in handling unemployment in Indonesia focuses more on microeconomic factors. This research is expected to contribute to the analysis of the unemployment rate in Indonesia in the study of business and microeconomics.